Antibacterial Efficacy of Myrtus communis Nanoemulsion Against Multidrug-Resistant, ESBL-Producing Pseudomonas aeruginosa and Its Association with β-Lactam Resistance Profiles - Dhulfiqar Abdulhussein Baqer Alkhawga (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Pseudomonas aeruginosa is a major opportunistic pathogen responsible for severe hospital-acquired infections and is increasingly associated with multidrug resistance mediated by extended-spectrum and metallo-β-lactamases. Specific Background: The rapid dissemination of ESBL- and MBL-producing P. aeruginosa has compromised the efficacy of third-generation cephalosporins and carbapenems, creating an urgent need for alternative antimicrobial strategies. Knowledge Gap: Evidence remains limited regarding the effectiveness of phytochemical nanoemulsions against genetically characterized MDR P. aeruginosa isolates. Aims: This study evaluated the antibacterial activity of a Myrtus communis essential oil nanoemulsion against clinical ESBL-producing P. aeruginosa and examined its association with β-lactam resistance profiles. Results: Among 350 clinical samples, 40 P. aeruginosa isolates showed high resistance to cephalosporins and carbapenems, with prevalent VIM, IMP, CTX-M, and SHV genes. The formulated nanoemulsion exhibited a mean droplet size of 96.15 nm and demonstrated strong antibacterial activity, with a minimum inhibitory concentration of 0.07 mg/µL and a minimum bactericidal concentration of 0.2 mg/µL, effectively inhibiting most MDR isolates. Novelty: This study integrates molecular resistance profiling with nanoemulsion-based phytotherapy against MDR P. aeruginosa. Implications: Myrtle nanoemulsion represents a promising adjunct or alternative antimicrobial approach for managing life-threatening MDR infections, particularly in settings with limited therapeutic options.Highlight : ESBL and MBL genes were highly prevalent in multidrug-resistant P. aeruginosa. Myrtus communis nanoemulsion showed stable nanoscale properties. Low MIC and MBC values confirmed strong antibacterial activity. Keywords : Pseudomonas aeruginosa, Myrtus communis nanoemulsion, Antibiotic resistance, ESBL and MBL genes, Antibacterial activity